Intestinal secretory and absorptive function in Trichinella spiralis mouse model of postinfective gut dysfunction: role of bile acids. Issue 1 (3rd August 2007) - Kalia, N; Hardcastle, J; Keating, C; Pelegrin, P; Grundy, D; Grasa, L; Bardhan, K D
Abstract : Objective: Observations showing that bile acid malabsorption is frequent in irritable bowel syndrome (IBS) suggest that alterations in bile acid-induced secretion and absorption could contribute to IBS-associated diarrhoea. The secretory response to bile acids, fluid transport and bile absorption was examined in intestinal tissues from a Trichinella spiralis mouse model of postinfectious gut dysfunction in vitro . Changes in the protein expression of apical sodium-dependent bile acid transporter (ASBT) were also measured. Design: T. spiralis -infected mice were killed at 18 and 25 days postinfection. Jejunal, ileal, proximal and distal colon segments were exposed to taurodeoxycholic acid (TDCA) or cholic acid. Short circuit current (SCC) increases were determined. Tritiated taurocholic acid (3H-TCA) absorption was determined in everted jejunal and ileal sacs. ASBT protein expression was determined by Western blot analysis and immunohistochemistry. Results: Basal SCC increased in ileum and distal colon at 18 and 25 days postinfection, respectively. Ileal SCC responses to TDCA and cholic acid were enhanced at 18 days postinfection. Distal colon SCC response to TDCA was raised at 18 days postinfection but was significantly reduced by 25 days. Ileal 3H-TCA uptake was significantly reduced at 18 and 25 days postinfection. Surprisingly, increased ASBT expression was observed in infected animals. Conclusions: In a T. spiralis model of postinfectious gut dysfunction, decreased bile absorption and enhanced secretion in response to bile acids was observed. Decreased absorption was not, however, caused by decreased ASBT as increased expression was observed. If similar events occur postinfection, the combined effects of these disturbances may contribute to some symptoms observed in postinfectious IBS patients.